ALgebra#2

Algebra Level 1

If a 3 + b 3 + c 3 3 a b c = 48 a^3+b^3+c^3-3abc =48 and 3 ( a + b + c ) ( a b + b c + c a ) = 99 3(a+b+c)(ab+bc+ca)=99 , find ( a + b + c ) 3 (a+b+c)^3 .


The answer is 147.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jul 22, 2018

Note that:

( a + b + c ) 3 = a 3 + b 3 + c 3 + 3 ( a + b + c ) ( a b + b c + c a ) 3 a b c = 48 + 99 = 147 \begin{aligned} (a+b+c)^3 & = {\color{#3D99F6}a^3+b^3+c^3} + {\color{#D61F06}3(a+b+c)(ab+bc+ca)} \color{#3D99F6} -3abc \\ & = {\color{#3D99F6} 48} + \color{#D61F06}99 \\ & = \boxed{147} \end{aligned}

X X
Jul 21, 2018

3 ( a + b + c ) ( a b + b c + c a ) = 3 ( a 2 b + a b 2 + b 2 c + b c 2 + c 2 a + c a 2 ) + 9 a b c {\color{#3D99F6}3(a+b+c)(ab+bc+ca)}=3{\color{#D61F06}(a^2b+ab^2+b^2c+bc^2+c^2a+ca^2)}+9{\color{#EC7300}abc}

( a + b + c ) 3 = a 3 + b 3 + c 3 + 3 ( a 2 b + a b 2 + b 2 c + b c 2 + c 2 a + c a 2 ) + 6 a b c (a+b+c)^3={\color{#20A900}a^3+b^3+c^3}+3{\color{#D61F06}(a^2b+ab^2+b^2c+bc^2+c^2a+ca^2)}+6{\color{#EC7300}abc}

= a 3 + b 3 + c 3 + 3 ( a 2 b + a b 2 + b 2 c + b c 2 + c 2 a + c a 2 ) + 9 a b c 3 a b c ={\color{#20A900}a^3+b^3+c^3}+3{\color{#D61F06}(a^2b+ab^2+b^2c+bc^2+c^2a+ca^2)}+9{\color{#EC7300}abc}-3{\color{#EC7300}abc}

= ( a 3 + b 3 + c 3 3 a b c ) + 3 ( a + b + c ) ( a b + b c + c a ) = 48 + 99 = 147 =({\color{#20A900}a^3+b^3+c^3}-3{\color{#EC7300}abc})+{\color{#3D99F6}3(a+b+c)(ab+bc+ca)}=48+99=147

48+99=147, not 48+9=147.

Vaibhav Priyadarshi - 2 years, 10 months ago

Log in to reply

Typo.Thanks.

X X - 2 years, 10 months ago

Note that a 3 + b 3 + c 3 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c a c ) . a^3 + b^3 + c^3 - 3abc = (a+b+c)(a^2 + b^2 + c^2 -ab - bc -ac).

So ( a + b + c ) ( a 2 + b 2 + c 2 a b b c a c ) = 48 ; ( a + b + c ) ( a b + b c + a c ) = 33 (a+b+c)(a^2 + b^2 + c^2 -ab - bc -ac)=48; (a+b+c)(ab+bc+ac)=33

( a b + b c + a c ) = 33 a + b + c . (ab+bc+ac)=\dfrac{33}{a+b+c}.

( a + b + c ) ( a 2 + b 2 + c 2 ) ( a + b + c ) ( a b + b c + a c ) = 48 \implies (a+b+c)(a^2 + b^2 + c^2) -(a+b+c)(ab+bc+ac) = 48 ( a + b + c ) ( a 2 + b 2 + c 2 ) 33 = 48 \implies (a+b+c)(a^2 + b^2 + c^2) - 33=48 ( a + b + c ) ( a 2 + b 2 + c 2 + 2 ( a b + b c + a c ) ) = 81 + 66 \implies (a+b+c)(a^2 + b^2 + c^2 + 2(ab+bc+ac)) = 81 + 66 ( a + b + c ) 3 = 147 . \implies (a+b+c)^3=\boxed{147}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...